2003
DOI: 10.1046/j.1525-1314.2003.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting metamorphic evolution of metasedimentary rocks from the Çine and Selimiye nappes in the Anatolide belt, western Turkey

Abstract: P–T conditions, mineral isograds, the relation of the latter to foliation planes and kinematic indicators are used to elucidate the tectonic nature and evolution of a shear zone in an orogen exhumed from mid‐crustal depths in western Turkey. Furthermore, we discuss whether simple monometamorphic fabrics of rock units from different nappes result from one single orogeny or are related to different orogenies. Metasedimentary rocks from the Çine and Selimiye nappes at the southern rim of the Anatolide belt of wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 55 publications
(163 reference statements)
6
76
2
Order By: Relevance
“…Hetzel & Reischmann (1996) showed that 40 Ar/ 39 Ar muscovite ages of 35-43 Ma constrain slow Eocene cooling during and after movement at the Selimiye shear zone. Subsequently, Ring et al (1999a), Gessner et al (2001c and Régnier et al (2003) supplied Figure 1. Simplified tectonic map of Anatolide belt in western Turkey (this region is traditionally referred to as Menderes Massif ); subdivison of region into three submassifs (Gördes submassif,Ödemiş submassif, which occupies same area as the Central Menderes metamorphic core complex, and Ç ine submassif) follows Şengör (1987).…”
Section: B the Menderes Nappesmentioning
confidence: 91%
See 3 more Smart Citations
“…Hetzel & Reischmann (1996) showed that 40 Ar/ 39 Ar muscovite ages of 35-43 Ma constrain slow Eocene cooling during and after movement at the Selimiye shear zone. Subsequently, Ring et al (1999a), Gessner et al (2001c and Régnier et al (2003) supplied Figure 1. Simplified tectonic map of Anatolide belt in western Turkey (this region is traditionally referred to as Menderes Massif ); subdivison of region into three submassifs (Gördes submassif,Ödemiş submassif, which occupies same area as the Central Menderes metamorphic core complex, and Ç ine submassif) follows Şengör (1987).…”
Section: B the Menderes Nappesmentioning
confidence: 91%
“…The Selimiye nappe contains Palaeozoic metapelite, metabasite and marble (Schuiling, 1962;Ç aǧlayan et al 1980;Loos & Reischmann, 1999;Régnier et al 2003). Most of the Ç ine nappe consists of deformed orthogneiss, largely undeformed metagranite and minor pelitic gneiss, eclogite and amphibolite.…”
Section: B the Menderes Nappesmentioning
confidence: 99%
See 2 more Smart Citations
“…The Menderes Nappes consists of four individual nappes, which, and this is an important point of our review, do not show any signs for a high-pressure overprint (Ring et al, 2001). It is important to note that detailed studies by various groups has demonstrated that the entire sequence below the two magneisocarpholite-kyanite-chloritoid bearing rocks does not show any relics for a high pressure overprint (Regnier et al, 2003), indicating that most probably the entire Menderes Nappes did not undergo high-pressure metamorphism.…”
Section: Anatolide Beltmentioning
confidence: 99%